2011
DOI: 10.3168/jds.2010-4048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human-animal relationship and management on udder health in Swiss dairy herds

Abstract: In a cross-sectional study, we investigated the effects of human-animal interactions and management factors on udder health in 46 Swiss dairy herds living in loose-housing systems on farms that participated in the Swiss dairy farm network "pro-Q." The human-animal relationship was measured by observing milkers' behavior, cows' behavior during milking, and cows' avoidance distance in the barn. Management factors were assessed by questionnaire-guided interviews and observations. Udder health was evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 47 publications
9
54
2
4
Order By: Relevance
“…Finally, kicking is also a reflection of pain and stress as SCC rise. Ivemeyer et al (2011) reported that herds with a higher incidence of new infections of mastitis showed more kicking during milking. Consequently, kicking was also associated with reduced milk yield.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, kicking is also a reflection of pain and stress as SCC rise. Ivemeyer et al (2011) reported that herds with a higher incidence of new infections of mastitis showed more kicking during milking. Consequently, kicking was also associated with reduced milk yield.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da inexistência de estudos que analisam o perfil de CCS entre os vários cruzamentos HZ, sabe-se que há diferença entre raças quanto à susceptibilidade à mastite (De Vliegher et al, 2004), sendo a raça Holandesa a mais susceptível (Berry et al, 2007, Ivemeyer et al, 2011 Sci., v.91, p.4437-4439, 2008. …”
Section: Resultsunclassified
“…Aproximadamente 30% dos rebanhos brasileiros produzem leite com CCS de tanque acima de 600.000 cél./mL (Santos, 2013), o que, segundo Schwarz et al (2010), indica alta prevalência de mastite subclínica no rebanho. Independentemente da duração do problema, esse resulta em perdas de produção de leite e alterações na composição e qualidade dele, devido ao processo inflamatório que ocorre na glândula mamária (Ivemeyer et al, 2011). Segundo Philpot (2002), estima-se que, para cada aumento de 100.000 cél./mL na CCS, acima do limite apresentado pela literatura (200.000 cél./mL -Harmon, 1994), ocorra uma perda de produção de leite de aproximadamente 2,5%.…”
Section: Introductionunclassified
“…Dass die Einstellung und das Verhalten des Landwirtes Einfluss auf die Eutergesundheit haben, zeigten auch Studien von Jansen et al [37], Ivemeyer et al [38] und Schewe et al [39]. Tschopp et al [35] konnten zeigen, dass die Auseinandersetzung des Landwirts selbst mit Tiergesundheitsthemen zu einer Reduktion von antibiotischen Mastitisbehandlungen führte, während punktuelle Inanspruchnahme von Beratung oder regelmässige Betreuung durch den Hoftierarzt keinen Einfluss zeigten oder sogar zu einer Erhöhung der eingesetzten Antibiotikamenge führten.…”
Section: Diskussionunclassified